(untitled) (Eurasian Scientific Herald, 2022)
The junction of wooden columns with the foundation is the most responsible part. The strength of a wooden column attached to the foundation with metal rods attached to it depends on the stress-strain state of the elements used under the influence of longitudinal load and bending moment. The article presents the results of experimental testing of the compressive strength and deformation of glued metal rod joints used in the connection of columns.